ANALISIS KRITIS PENGUATAN RUANG PUBLIK INKLUSIF MELALUI KONTRIBUSI KOMUNITAS LITERASI DI KOTA SURAKARTA - Sukma Wisnu Pamungkas; Fauzi Annur; Muhammad Munadi (Universitas Islam Negeri Salatiga, 2026)
This study aims to critically analyze the contribution of literacy communities in strengthening inclusive public spaces in the city of Surakarta. Departing from the low national literacy rate and the limited access to reading facilities in open spaces, this research highlights how citizen-led communities independently initiate literacy practices outside formal institutions. Using a qualitative approach with a case study method, the study explores the activities of three active literacy communities, namely Bakaran, Solo Book Party, and Sobomaos, through participatory observation, in-depth interviews, and activity documentation. The findings show that these communities have successfully reclaimed public spaces such as city parks, campus courtyards, angkringan stalls, and cafés into collective learning spaces that are non-hierarchical, inclusive, and reflective. Literacy in this context is no longer understood merely as a technical ability, but as a social, political, and spatial practice that strengthens learning culture, civic participation, and community empowerment. Despite facing structural challenges such as limited policy and infrastructural support, the communities demonstrate resilience and innovation. As an applied contribution, this research recommends the development of a “Taman Cerdas” as a public literacy ecosystem that integrates recreational, technological, and educational functions within an environmentally friendly open space accessible to all citizens. These findings show that community-driven literacy can serve as a model for urban development rooted in citizen participation and oriented toward spatial justice.